Enhancement of redox stability and electrochromic performance of aromatic polyamides by incorporation of (3, 6‐dimethoxycarbazol‐9‐yl)‐triphenylamine units. Issue 2 (25th November 2013) - Wang, Hui‐Min; Hsiao, Sheng‐Huei
ABSTRACT New series aromatic polyamides with (carbazol‐9‐yl)triphenylamine units were synthesized from a newly synthesized diamine monomer, 4, 4′‐diamino‐4″‐(3, 6‐dimethoxycarbazol‐9‐yl) triphenylamine, and aromatic dicarboxylic acids via the phosphorylation polyamidation technique. These polyamides exhibit good solubility in many organic solvents and can be solution‐cast into flexible and strong films with high thermal stability. They show well‐defined and reversible redox couples during oxidative scanning, with a strong color change from colorless neutral form to yellowish green and blue oxidized forms at applied potentials scanning from 0.0 to 1.3 V. They show enhanced redox‐stability and electrochromic performance as compared to the corresponding analogs without methoxy substituents on the active sites of the carbazole unit. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 272–286